IT Governance Capability Assessment Using COBIT 2019 Framework in STIKI Malang Library Information Systems - Christian, Timoty Des; Gyofany, Mochamad Dwi Oxta; Allbani, Muhammad Bagas (J-INTECH (Journal of Information and Technology), 2023)
STIKI Malang Library, as a library service manager, requires a capability level review, especially on IT risk aspects, a review of service policies, and the quality of human resources. This study aims to analyze the level of capability and provide recommendations using the COBIT 2019 framework. Data were collected through interviews with the Head of the Library and Staff of Information Systems and Information Technology at STIKI Malang and IT governance document analysis. APO12, BAI10, and DSS04 were chosen based on COBIT 2019 design factors. The results show that these three objectives are currently at level three, with a target of level four. STIKI Malang Library can achieve this target by improving IT risk management, regular reporting to the management, and identifying required resources for business continuity.